Description Of Students' Learning Attitude Stikes Karsa Husada Garut On Hybrid Learning - Sri Yekti Widadi; Anjas Bahtiar (Jurnal EduHealth, 2023)
DESCRIPTION OF STUDENTS' LEARNING ATTITUDE STIKES KARSA HUSADA GARUT ON HYBRID LEARNING   ABSTRACT   Covid-19 which has had a huge impact on education in Indonesia, lessons that were originally face-to-face between teachers and students turned into online learning, in order to minimize the spread of the covid-19 virus. When the covid virus can be handled, the education level changes in learning itself into hybrid learning where hybrid learning itself is to minimize the spread of covid-19. Hybrid learning is a learning model that involves two learning methods, namely online and face-to-face, where each class is divided into two in conducting hybrid learning. Attitude is the tendency to act, perceive, think, and feel in the face of objects, ideas, situations or values. A very positive attitude from students is one of the keys to the implementation of the learning process. The purpose of this study is to describe the learning attitudes of STIKes Karsa Husada Garut students in hybrid learning. The research method used in this research is using a cross sectional research design with a random sampling technique using the Startified Random Sampling method as many as 95 respondents. Data were collected using a questionnaire statement of student learning attitudes and the results showed that students' learning attitudes with good categories were 46 respondents (48.6%) and 49 respondents (51.6%).